Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve this proportion for x:
(2x-3)x=2(x^2-6)


Sagot :

(2x - 3)x = 2(x² - 6)
     +6                +6
(2x + 3)x = 2(x²)
(2x)x + (3)x = 2x²
2x² + 3x = 2x²
-2x²         -2x²
         3x = 0
          3     3
           x = 0